HUBUNGAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN - Dwi Kartikasari; Citra Mawardika Asellawati Siregar (Politeknik Negeri Batam, 2017)
This aims of the study is determine the relationship between corporate social responsibility on corporate financial performance (empirical studies on PT. Citra Tubindo Tbk and PT. Sat Nusapersada Tbk in 2010-2014). The financial performance is measured by using a Return on Assets (ROA). This study uses a qualitative approach to data analysis using descriptive analysis and Scatterplott (scatter diagram). The data used are secondary data to analyze the data in the form of annual reports. The results of this study indicate Corporate Social Responsibility (CSR) has variety relationship to the Return on Assets (ROA).